Measuring Economic Openness - Claudius Gräbner; Philipp Heimberger; Jakob Kapeller; Florian Springholz (The Vienna Institute for International Economic Studies (wiiw), 2018)
A Review of Existing Measures and Empirical Practices This paper surveys existing measures of economic openness understood as the degree to which non-domestic actors can or do participate in a domestic economy. We introduce a typology of openness indicators which distinguishes between 'real' and 'financial' openness as well as between 'de facto' and 'de jure' measures of openness, and show that this classification indeed captures different dimensions of economic openness. The main contribution of the paper is to supply a comprehensive and novel data set of openness indicators available for interested researchers. Based on this effort, we analyse some trends in economic openness over time and provide a correlation analysis across indicators. Finally, we explore the practical implications of choosing from different openness measures within a growth regression framework and highlight that researchers should make the choice of the indicator based on explicit theoretical justifications that correspond to their specific research questions.
Keywords: F00; F40; F60; 330; economic openness; trade openness; financial openness; globalisation